Long-Term Retrospective Analysis of Microvascular Decompression in Patients With Recurrent Trigeminal Neuralgia - Liu, Jiayu; Wu, Guangyong; Xiang, Hui; Liu, Ruen; Li, Fang; Hei, Bo; Qian, Weiqiang; Song, Haidong; Liu, Zhi (Frontiers in Neurology, 2020)
Objective: To explore the clinical characteristics of patients with recurrent trigeminal neuralgia (TN) and the experience of microvascular decompression (MVD) in the treatment of such patients. Methods: We retrospectively analyzed clinical data, imaging examination results, surgical methods and treatment efficacies in 127 patients with recurrent typical TN from January 2005 to December 2014. Results: The age of the recurrent group was higher than that of the nonrecurrent group (p<0.05). The duration of pain before the first MVD procedure was longer in the recurrent group than in the nonrecurrent group (p<0.05). Patients in the recurrent group were more likely to have compression of the vertebrobasilar artery (VBA) or multiple vessels than patients in the nonrecurrent group (p<0.05). A Kaplan–Meier curve showed a median pain-free survival of 12 months after the first MVD procedure. The severity of pain (preoperative visual analog scale [VAS] score) in patients with recurrence was lower than that in patients with first-onset TN (p<0.05). Vessel compression, Teflon compression or granuloma and arachnoid adhesion were considered the main causes of recurrence. Postoperative Barrow Neurological Institute (BNI) scores in the redo MVD group were excellent (T = 2) for 69 patients (53.33%) and good (T = 3) for 46 patients (36.22%). The postoperative follow-up was 63 to 167 months (105.92±25.66). During the follow-up, no recurrence was noted. All complications were cured or improved. Conclusions: MVD is an effective surgical method for the treatment of TN and has been widely accepted by neurosurgeons in the last ten years worldwide. For recurrent patients, reoperation can achieve good results.